2019
DOI: 10.1002/prop.201900068
|View full text |Cite
|
Sign up to set email alerts
|

A Note on the dS Swampland Conjecture, Non‐BPS Branes and K‐Theory

Abstract: We point out that the de Sitter swampland conjecture would be falsified if classical fluxed Type IIA orientifold vacua with a single non‐BPS D7‐brane were indeed part of the string theory landscape. In other words, the dS swampland conjecture implies the cancellation of K‐theory charges on a compact space.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 53 publications
0
21
0
Order By: Relevance
“…for the number of NS5-branes on the heterotic side. 11 The apparent controversy of this example demonstrates that starting with incomplete cobordism structures has its limitations, but still has the potential to uncover new aspects of string theory. (5.28)…”
Section: Spinmentioning
confidence: 99%
See 2 more Smart Citations
“…for the number of NS5-branes on the heterotic side. 11 The apparent controversy of this example demonstrates that starting with incomplete cobordism structures has its limitations, but still has the potential to uncover new aspects of string theory. (5.28)…”
Section: Spinmentioning
confidence: 99%
“…10 Actually, for n odd, F n is not Spin and one has an additional non-trivial line bundle on the Spin c -manifold. 11 Coming back to the discussion around eq. (5.26), for B = dP 9 we obtain n T = 9 which is indeed the result for the Ωσ orientifold of [35].…”
Section: Comment On Gauging the Global Symmetry Of ω Spinmentioning
confidence: 99%
See 1 more Smart Citation
“…The refined version of the conjecture was motivated by stability of de Sitter extrema [8], by cosmological arguments through the slow-roll parameter η V [9], as well as by entropy arguments together with the distance conjecture on the dS space [10]. Many logic and solid arguments have been followed in the literature [11][12][13][14][15][16][17][18][19][20] so far with the purpose to give stronger ground basis to this conjecture. A matter of particular interest to us is the series of arguments supporting the de Sitter conjecture (dSC) based on the laws of thermodynamics [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it is known that fractional fluxes in string compactifications could be essential to reproduce inflation and decide wether the considered model is in or out the Swampland. Within this context it was also shown that the refined dS Conjecture is not valid in the presence of non-BPS states when the corresponding K-theory charged is not cancelled in the compact internal space [8].…”
Section: Introductionmentioning
confidence: 99%